Strategy in contests: an introduction; Strategie in Turnieren – eine Einführung - Kai A. Konrad (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
Competition in which goods or rents are allocated as a function of the various efforts expended by players in trying to win these goods or rents is a very common phenomenon. A subset of examples comes from marketing, litigation, relative reward schemes or promotion tournaments in internal labor markets, beauty contests, influence activities, education filters, R&D contests, electoral competition in political markets, military conflict and sports. I survey here this type of competition which is sometimes called contest or tournament. I focus on the role of its various design aspects, such as prize structure, sequencing, nesting, repetition, elimination contests and many others. Some key insights about the nature and properties of this type of competition emerge from this analysis. – – Die Arbeit behandelt strategische Entscheidungen in Turnier- und Wettkampfsituationen. Sie gibt einen theoretischen und empirischen Überblick und ergänzt die umfangreiche theoretische Literatur zu diesem Thema, besonders in Hinblick auf wiederholte Turniere und auf komplexere Wettbewerbsstrukturen, die sich aus verschiedenen gestaffelten Einzelturnieren zusammensetzen.
Keywords: D72; D74; 330; Survey of contests; tournaments; conflict; strategic aspects